A five channels SiC MUX/DEMUX device with channel separation in the visible range - Vieira, Manuela (2019)
In this paper we present a tandem UV/VIS/ NIR wavelength selector based on a multilayer a-SiC:H optical filter that requires appropriate ultraviolet steady states optical switches to select the desired wavelengths in the ultraviolet/visible/infrared spectral ranges. Five ultra-light communication channels are transmitted together, each one with a specific bit sequence. Results show that the background side and intensity works as a selector in the infrared, visible and ultra violet light regions, shifting the sensor sensitivity. This nonlinearity allows the identification and decoding of the different input channels. This concept is extended to implement a 1 by 5 wavelength division multiplexer with channel separation in the visible range and a transmission capability of 30 Kbps. The relationship between the optical inputs and the output signal is established and an algorithm to decode the MUX signal presented.